Ectopic Pregnancy: A Review of Prevalence, Clinical Presentation and Outcome in Gusau, Northwest, Nigeria - Shittu MA; Olaoye SO; Aremu-Kasumu YB; Fasanu OT (Ibom Medical Journal)
Background: The prevalence of ectopic pregnancy in Zamfara state is unknown and gynaecological emergency admissions for this condition are on the increase.